2018
DOI: 10.1109/tnb.2018.2869124
|View full text |Cite
|
Sign up to set email alerts
|

End-to-End Noise Model for Intra-Body Terahertz Nanoscale Communication

Abstract: In vivo wireless nanosensor networks (iWNSNs) are paving the way toward transformative healthcare solutions. These networks are expected to enable a plethora of applications, including drug-delivery, bio-sensing, and health monitoring. With the development of miniature plasmonic signal sources, antennas, and detectors, wireless communications among intrabody nanodevices will expectedly be enabled in the terahertz (THz) frequency band (0.1-10 THz). Several propagation models were recently developed to analyze a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…In particular, the authors in [196] presented an attenuation model of intrabody THz propagation to facilitate the accurate design and practical deployment of iWNSNs. In subsequent studies, the authors also demonstrated both the photothermal impact [197] along with the noise effect [198] of THz intrabody communication to further verify the feasibility and prosperity of such propagation mechanism.…”
Section: A Terahertz Nanoscale Applicationsmentioning
confidence: 87%
“…In particular, the authors in [196] presented an attenuation model of intrabody THz propagation to facilitate the accurate design and practical deployment of iWNSNs. In subsequent studies, the authors also demonstrated both the photothermal impact [197] along with the noise effect [198] of THz intrabody communication to further verify the feasibility and prosperity of such propagation mechanism.…”
Section: A Terahertz Nanoscale Applicationsmentioning
confidence: 87%
“…The statistics of error prediction in terms of standard deviation and mean were presented and the results were found to agree well with the measured ones. A stochastic model that considers different forms of noise that may impact propagation within nano scale systems was considered by Elayan et al [246] by deriving probability distributions of the noise sources. It was found that Doppler induced noise has the greatest contribution compared to other sources of noise such as black body noise and Johnson-Nyquist noise.…”
Section: ) Hst Communicationsmentioning
confidence: 99%
“…As is for any communication systems, THz systems are impacted by noise, interference [21]- [24], and pointing errors [10], [11], [25], [26]. The effect of pointing errors at higher frequencies is inevitable even with highly directional signal beams.…”
Section: A Related Workmentioning
confidence: 99%